Pengaruh Pemanfaatan Teknologi Informasi, Pengetahuan Karyawan Bagian Akuntansi dan Pelatihan Sebagai Variabel Kontrol terhadap Efektivitas Sistem Informasi Akuntansi - Vina Hariyati; Cris Kuntadi; Rachmat Pramukty (Universitas Kristen Indonesia Toraja, 2023)
in this article the factors that influence the effectiveness of the Accounting Information System, namely Information Technology Utilization, Knowledge of Accounting Employees and Training as Control Variables, a literature study of Accounting information systems. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Information Technology Utilization affects the Effectiveness of Accounting Information Systems; 2) Knowledge of Accounting Section Employees affects the Effectiveness of Accounting Information Systems; and 3) Training as a Control Variable affects the Effectiveness of the Accounting Information System.